Associations between 24-hour activity behaviours and emotional and behavioural problems of left-behind children: a component analysis of data from a cross-sectional study - Rui Li; Bin Lu; Zan Huang; Jiaying Lou; Yulan Zhou (BMJ Open)
Objectives This study employed compositional data analysis to examine the association between 24-hour activity behaviours and emotional and behavioural problems among left-behind children (LBC).Design Cross-sectional analysis.Setting The research used a cross-sectional approach to analyse data collected from LBC living in Ningbo, Zhejiang Province, southern China, between February and May 2023.Participants A total of 275 LBC aged 9–15 years old were recruited.Outcome measures The measurement of 24-hour activity behaviour, incorporating sleep, sedentary behaviour (SED), light physical activity (LPA) and moderate-to-vigorous physical activity (MVPA), was accomplished using accelerometers. Emotional and behavioural problems were assessed through the application of the Strengths and Difficulties Questionnaire. Compositional data analysis was used to evaluate the potential relationship between the composition of 24-hour activity and emotional and behavioural problems.Results Changes in allocation, such as transferring time from SED to sleep and LPA, were associated with better internalising (β sleep=−0.53, 95% CI −0.60 to −0.46; β LPA=−0.46, 95% CI −0.55 to −0.38) and externalising problems (β sleep=−0.31, 95% CI −0.39 to −0.22; β LP =−0.23, 95% CI −0.32 to −0.13). Furthermore, reallocating time from LPA to MVPA was associated with reduced internalising problems (β=−0.40, 95% CI −0.84 to −0.12). Positive associations with prosocial behaviour were observed when the time was reallocated to MVPA from sleep (β=0.81, 95% CI 0.57 to 1.05), SED (β=0.75, 95% CI 0.51 to 0.99) and LPA (β=0.82, 95% CI 0.57 to 1.08).Conclusions The composition of 24-hour activity behaviours is correlated with emotional and behavioural problems in LBC. The findings indicate that redistributing time from SED to sleep and LPA is linked to improved internalisation and externalisation problem scores. Additionally, the substitution of MVPA for any other behaviours is positively associated with enhanced prosocial behaviours.